Penggunaan Deiksis Dalam Film Divergent Karya Neil Burger: Analisis Pragmatik - Alfisyahrin, Dilla Resha (Aksara: Jurnal Bahasa dan Sastra, 2025)
Without us realizing, deixis are used in a daily life in utterance with interlocutors, including utterance of the characters in the movies. This research analyzes deixis in the Divergent movies by Neil Burger using a pragmatic approach. This study aims to analyse and classify the types of deixis and the functions. This research method used is a descriptive qualitative method. The data collection technique are listening and note-taking method. Based on the results analysis in the Divergent movies by Neil Burger, five types of deixis were found: (1) persona deixis, (2) spatial deixis, (3) temporal deixis, (4) social deixis, and (5) discourse deixis.  Keywords: Movies, utterances, pragmatic, deixis